P.073 Improving access to urgent neurology care for pediatric patients. (5th June 2019) - Yaworski, A; Yager, J; Mailo, J; Richer, L; Rajapakse, T; Kassiri, J
Abstract : Background: Pediatric neurology referral wait times are increasing, often leading to emergency department (ED) utilization. On average 5% of ED patients present with neurological symptoms and 35% of ED neurological diagnoses are revised after specialist review. A Stollery Rapid Access Neurology (RAN) clinic was created to decrease wait time, and initiate an efficient referral process.Methods: The RAN clinic ran weekly from March 2018 until February 2019. This was a prospective study approved by the University of Alberta ethics board. Inclusion criteria were met. Information was collected for diagnosis, along with confidential patient satisfaction surveys.Results: Seventy-five patients were referred, 49% from the ED. Wait time averaged 6 weeks. The most frequent referral reason was seizures, with 60% of referring diagnosis being correct. Prior to RAN appointment, 61% of patients presented to the ED, whereas only 0.1% returned in the following 3 months. Neurology follow up was required in 81% of patients. Overall satisfaction was ranked 9.6/10.Conclusions: The RAN clinic created an effective urgent triage method. Neurologist review revised 40% of diagnoses. This ongoing study reveals that a RAN clinic can reduce visits to the ED following appointment and initiate appropriate follow up. Future evaluation in cost effectiveness and telehealth appointments are required.